ChemInform Abstract: 2‐Allylaminothiazole and 2‐Allylaminodihydrothiazole Derivatives: Synthesis, Characterization, and Evaluation of Bioactivity. Issue 14 (March 2016) - Studzinska, Renata; Karczmarska‐Wodzka, Aleksandra; Kozakiewicz, Anna; Kolodziejska, Renata; Paprocka, Renata; Wroblewski, Marcin; Augustynska, Beata; Modzelewska‐Banachiewicz, Bozena
Abstract: 2‐Allylaminodihydrothiazole derivatives (III) are synthesized by condensation of allylthiourea (I) with haloesters (II) in alkaline medium, whereas 2‐allylaminothiazole derivatives (V) are obtained by condensation of (I) with chlorooxoesters (IV) via acetal as intermediate compound, both of them with good yields.